Vaginal Calculi in the Eastern North Atlantic Common Dolphins Delphinus Delphis, Induction Mechanisms and Possible Effects on Fecundity - Dabin, Willy; Rochowski, Bastien; Daudon, Michel; Ridoux, Vincent (Frontiers in Marine Science, 2021)
The proper management of cetacean populations requires life history and demographic parameters to be estimated at population level. In this study we focus on a reproductive pathology that has the potential to alter reproductive rate: the vaginal calculi or stones. The present work documents vaginal calculi prevalence and structure in the eastern North Atlantic common dolphin Delphinus delphis in order to infer their likely mechanisms of induction and possible effects on fecundity. The work is based on routine examinations and necropsies of stranded marine mammals reported by the French stranding scheme from 1972-2012. Vaginal calculi were described and measured, and their composition was analysed by Fourrier-Transformed Infra-Red (FTIR) spectroscopy. Necropsies and reproductive tract examinations were performed on 435 female common dolphins since 1972 along the French coasts, of which 14 showed vaginal calculi, representing 3.2% of the examined females. All females with calculi were older than 7, and there was no relationship of calculus size with age. Histopathology revealed lesions due to an inflammatory response to the presence of the calculi: chronicle vaginitis, variable endometritis and cystitis. Calculus size varied from 1-21 cm in maximum dimension and 4-1460 g in mass. Their internal structure was homogeneous, particularly due to the absence of core material, hence corresponding to the definition of primary calculi. All calculus spectra showed almost identical compositions, with struvite (magnesium ammonium phosphate hexahydrate) representing on average 87% of calculus mass. Dysfunction of the uro-genital tract, such as vesico-vaginal fistulae, would be the likely initial pathological condition that led to the formation of these stones. Both the initial chemical condition in the vagina and the resulting formation of a calculi are obstacles to successful reproduction.